ENHANCING MOBILITY WITH IOT-BASED AUTONOMOUS WHEELCHAIR - Namiq Ahmmed, Zhwan; Qader Kheder, Mohammed (Science Journal of University of Zakho, 2024)
The shortage of healthcare workers and continuous influx of patients have significantly increased workloads in hospitals. Concurrently, there is an increasing number of people with disabilities, resulting in a higher need for wheelchairs. Yet, many hospitals continue to rely on traditional, manually operated wheelchairs. As a result, disabled patients often face prolonged waits for assistance from hospital staff to reach their intended destinations. To address hospital issues, the idea of autonomous wheelchairs, known as autonomous robotic wheelchairs (ARWs), has been proposed and developed. In contrast to traditional wheelchairs, ARWs integrate advanced features, including obstacle detection and avoidance, local path mapping through line-following technology, and user-friendly interactions. Patients in developing countries, including the Kurdistan region of Iraq (KRI), rely on hospital workers for transportation, which poses difficulties, especially during emergencies, such as overcrowding, delays due to a lack of available porters, etc. Implementing ARWs would significantly reduce these issues. Thus, the main aim of this study is to develop ARWs using technologies like Arduino and sensors to enhance hospital efficiency and reduce reliance on porters, potentially transforming patient mobility and care in healthcare facilities. The testing results of the proposed system indicate that its implementation will greatly assist hospitals in addressing various issues, including those previously mentioned. In addition, it will enhance hospitals’ intelligence and autonomy.